Politics embodied: How politics shapes and is shaped by the bodily experience of emotions - Andrea Vik; Alejandro Galvez-Pol; Sohee Park; Manos Tsakiris (Proceedings of the National Academy of Sciences, 2026)
Political emotions are widely acknowledged as key drivers of political participation and polarization. Yet while it is well established that political emotions matter, far less is known about how they are felt and represented in the body. Across a preregistered, nationally representative study ( N = 992), we introduce an embodied approach to political emotion using the validated emBODY-tool, which allows participants to map where in the body they experience sensations when feeling canonical emotions (e.g., anger) and their political counterparts (e.g., “political anger”). Specifically, we address three questions: 1) how political emotions are embodied and differ from their nonpolitical counterparts, 2) whether political dispositions influence how these political emotions are embodied, and 3) how their embodied experience interacts with political dispositions in explaining political attitudes and behavior. Pixelwise bodily sensation maps and aggregated “embodied impact” metrics show that political anger, anxiety, depression, disgust, and hope do not merely mirror their canonical forms, but take on distinct bodily patterns. Political ideology, but not political sophistication, modulates these bodily experiences, with Democrat-leaning participants reporting more intense sensations for negative political emotions, suggesting the presence of “ideological bodies.” Crucially, political participation is not explained by how intensely people report feeling emotions, but is instead closely linked to how strongly these emotions are embodied in the body. Together, our findings underscore the body’s central role in democratic engagement by showing how political contexts shape embodied emotional experience and how these embodied experiences shape politics and democracy.